A estrutura regulatória de economia solidária entre a cooperação social, o funcionamento do mercado e a ordem política estatal - Alves, André Gomes de Sousa (2017)
This doctoral thesis aims to investigate the institutional arrangements arising from the solidarity economy enterprises that outsource up from the cyclical crises that affect the nuclear capitalist system. In particular seat, the analysis focuses on the joint initiatives resulting from instabilities that sharpen inequality and social exclusion processes, as well as on the description of the political, cultural and economic dimensions that derive from this phenomenon, so as to reach a better understanding of the juridical-jurigenos aspects that exist in this environment. Thus, using the hypothetical-deductive method of approach, methods of historical, functionalist and structuralist procedure, as well as techniques of literature and documentary research, this work aims to explain the immersion of the solidarity economy in the normative universe, highlighting the Law & Economics and Economic Law as reference for the explanation of the institutional designs which are limited therein. As a result, solidarity economy is understood as a socioeconomic phenomenon whose juridical normative complexity is dependent on the trajectory in which it was generated and, thus, related to a juridical pluralism that is circumscribed around the bonds of cooperative sociability, the functioning of the market and the state political order.